Panax notoginseng Attenuates the Infarct Volume in Rat Ischemic Brain and the Inflammatory Response of Microglia - Hye Young Son; Hyung Soo Han; Hyo Won Jung; Yong-Ki Park (Elsevier, 2009)
The roots of Panax notoginseng (PN) are commonly used as a therapeutic agent to stop hemorrhage and as a tonic to promote health in traditional Korean medicine. Stroke triggers an inflammatory response that not only plays a central role in the pathogenesis of cerebral ischemia, but also induces secondary damage. This study was designed to investigate the neuroprotective effects of the methanol extract of PN on the infarct volume induced by middle cerebral artery occlusion (MCAO) (90-min occlusion and 24-h reperfusion) in rat brains. The PN extract (50 mg/kg, i.p.) was administered 2 h after the onset of MCAO. The PN-treated groups had a reduction in infarct volume by 23.82 ± 8.9%. In the PN extract-treated groups, the microglial density was significantly decreased in the peri-infarct region; the underlying mechanism was inhibition of inflammatory mediators, such as inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2, via blocking of the NF-κB pathway. Furthermore, in vitro studies showed that the PN extract significantly reduced the production of iNOS-derived NO and COX-2- derived prostaglandin E2 through the regulation of gene transcription levels in primary microglia and BV-2 cells. These results suggest that anti-inflammatory and microglial activation inhibitory effects of the PN extract may contribute to its neuroprotective effects in brain ischemia. Keywords:: inflammation, microglia, Panax notoginseng, stroke